Emotion dysregulation and dyadic conflict in depressed and typical adolescents: Evaluating concordance across psychophysiological and observational measures - Crowell, Sheila E. (2014)
Many depressed adolescents experience difficulty regulating their emotions. These emotion regulation difficulties appear to emerge in part from socialization processes within families and then generalize to other contexts. However, emotion dysregulation is typically assessed within the individual, rather than in the social relationships that shape and maintain dysregulation. In this study, we evaluated concordance of physiological and observational measures of emotion dysregulation during interpersonal conflict, using a multilevel actor-partner interdependence model (APIM). Participants were 75 mother-daughter dyads, including 50 depressed adolescents with or without a history of self-injury, and 25 typically developing controls. Behavior dysregulation was operationalized as observed aversiveness during a conflict discussion, and physiological dysregulation was indexed by respiratory sinus arrhythmia (RSA). Results revealed different patterns of concordance for control versus depressed participants. Controls evidenced a concordant partner (between-person) effect, and showed increased physiological regulation during minutes when their partner was more aversive. In contrast, clinical dyad members displayed a concordant actor (within-person) effect, becoming simultaneously physiologically and behaviorally dysregulated. Results inform current understanding of emotion dysregulation across multiple levels of analysis.